Advances in the prevention of heterosexual transmission of HIV/AIDS among women in the United States - Nadine E. Chen; Jaimie P. Meyer; Sandra A. Springer (MDPI AG, 2011)
Despite recent advances in testing and treatment, the incidence of HIV/AIDS in the United States has remained stagnant with an estimated 56,300 new infections every year. Women account for an increasing proportion of the epidemic. The vulnerability of women to HIV stems from both increased biologic susceptibility to heterosexual transmission and also the social, economic, and structural disadvantages they often confront. This review describes the main reasons for the increased vulnerability of U.S. women to HIV transmission with particular emphasis on specific high-risk groups including: non-Hispanic blacks, women who use drugs, women with a history of incarceration, and victims of intimate partner violence. Although behavioral approaches to HIV prevention may be effective, pragmatic implementation is often difficult, especially for women who lack sociocultural capital to negotiate condoms with their male partners. Recent advances in HIV prevention show promise in terms of female-initiated interventions. These notably include female condoms, non-specific vaginal microbicides, and antiretroviral oral and vaginal pre-exposure prophylaxis. In this review, we will present evidence in support of these new female-initiated interventions while also emphasizing the importance of advocacy and the political support for these scientific advances to be successful.